I heard the voice of the Samaritan woman in John 4:1-46 - Cornelius, E (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
This article offers retellings of John’s story of the conversation between Jesus and the Samaritan woman. Two versions of this story are presented to be told by a female narrator, the Samaritan woman herself. The intention is to offer different perspectives on the same story, but most of all, to shed some light on a method of “hearing women’s voices” in male authored texts. In order to move the Samaritan woman to centre stage in the story of John 4:1-46, the first focus is John’s text to understand the character of the text, the author and readers of the text, the purpose, the different characters and the socio-historical background. Only then is the story retold from the woman’s perspective. The moment the woman is allowed to take centre stage, we are confronted by an ancient female perspective on women’s roles in society, a woman’s experience of Jesus, told in her own words, giving her own opinions, revealing her emotions and fears and joys. The rhetorical purpose of her text is not necessarily to bring about change in the hearts of people, but rather to reveal her own heart – her understanding of who Jesus was, her emotions during the conversation with Jesus, her opinions, her experience as a Samaritan woman in an ancient society, but most of all, the changes Jesus brought about in her life! She expresses her amazement at Jesus’ knowledge and most of all at his ignorance of the bounds and barriers of national hatred, revealing how he also crosses a religious boundary by simply talking to her – a Samaritan and a woman.